2010
DOI: 10.3390/su2103291
|View full text |Cite
|
Sign up to set email alerts
|

Cob Construction in Italy: Some Lessons from the Past

Abstract: Raw earth is a construction material unknown to most people. Nowadays, raw-earth constructions are an area of growing interest, both for rescuing the heritage and for a rediscovered environmentally friendly building and eco-sustainability material. However, because raw-earth constructions are a forgotten technique, we find problems of a lack of skilled people at all levels in this area, from designers to masons, as well as problems of how to carry out compatible conservation works on earthen heritage. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Earthen construction can be divided into four main categories: compressed earth block (CEB), rammed earth, adobe, and cob construction. While a lot of studies were published on the mechanical behaviour of rammed earth, CEB, and adobe [7,[21][22][23][24][25][26][27][28][29], very few researchers studied the mechanical properties of cob, which constitutes a diffuse alternative to rammed earth and adobe in specific geographical conditions [21,[30][31][32][33]. In fact, it is estimated that at least 200,000 units are constructed in EU by the cob technique, date back to the first half of the 20th century, the 19th century, the 18th century, and even older [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earthen construction can be divided into four main categories: compressed earth block (CEB), rammed earth, adobe, and cob construction. While a lot of studies were published on the mechanical behaviour of rammed earth, CEB, and adobe [7,[21][22][23][24][25][26][27][28][29], very few researchers studied the mechanical properties of cob, which constitutes a diffuse alternative to rammed earth and adobe in specific geographical conditions [21,[30][31][32][33]. In fact, it is estimated that at least 200,000 units are constructed in EU by the cob technique, date back to the first half of the 20th century, the 19th century, the 18th century, and even older [30].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning their mechanical behaviour, as already stated above, only few works can be found in the literature. In [31], the authors studied the compression and shear behaviour of still moist Italian cob walls (initial properties). However, no information was provided for walls in dried conditions.…”
Section: Introductionmentioning
confidence: 99%
“…al. tried to re-usethe Cob technique for construction and for how to accurately work on it for a suitable and sustainable conservation.the results of this study have found a suitable soil for future possible suitable restoring involvement on the investigated case study at Macerata, re-using the same old building technique, which is the most compatible involvement [6]. This work aims to study the effect of some additives on physical properties (watercontent% and thermal conductivity) and mechanical property (compression strength) of Cob.…”
Section: Effect Of Some Additives On Mechanical and Physical Propertimentioning
confidence: 83%
“…The Portuguese technique ''tabique'' [23] is some how similar to wattle and daub. As to the cob technique it involves mixing earth with straw and water to form layer by layer masonry walls [24]. Rammed earth means the compaction of moist earth (stabilized or not) inside a wooden formwork, although nowadays in Europe the steel formworks are replacing the wooden ones.…”
Section: Techniquesmentioning
confidence: 99%